Papuan Muslims in “One Furnace, There Stones” Metaphor in Fakfak Regency, West Papua Province: An Anthropolinguistic Perspective - Hugo Warami (RIRAI Publisher, 2022)
Religion should not be used as a legitimacy tool, particularly just as a justification for achieving goals that are full of the nuances of power politics, and the like. This study aims to reveal a tradition of Papuan Muslims in their attempts to create tolerance and harmony in the lives of religious people, which have been practiced and inherited for a long time, from generation to generation. This tradition is practiced by the Papuan Muslims in the Fakfak Regency, known as the “One Furnace, Three Stones” metaphor. This metaphor is used by the community in Fakfak as a moral consensus in the process of integration and social balance. The two approaches applied in this study are a theoretical approach and a methodological approach. The theoretical approach is an exploration of anthropolinguistic and metaphor theory; while the methodological approach is a descriptive approach with an explanative dimension. Based on the perspective of anthropolinguistic and metaphor, this study seeks to apply scientific principles to socio-cultural data, and adapts the steps of scientific studies in other fields of science. This study follows several procedures, including providing data, analyzing data, and presenting the results of data analysis. The results of this study holistically identify the issues of pluralism in Islam and Papuan culture, Islamic migration, metaphorical Papuan Muslim relations, and ideology. This study implies that it could be used as a basic reference in the practice of religious development which upholds tolerance and harmony between religious communities.